2011
DOI: 10.1007/s00421-011-1906-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic assessment of the acute phase of dystrophin deficiency in mdx mice

Abstract: Duchenne muscular dystrophy (DMD) is caused by the absence of a functional dystrophin protein and is modeled by the mdx mouse. The mdx mouse suffers an early necrotic bout in the hind limb muscles lasting from approximately 4 to 7 weeks. The purpose of this investigation was to determine the extent to which dystrophin deficiency changed the proteome very early in the disease process. In order to accomplish this, proteins from gastrocnemius from 6-week-old C57 (n = 6) and mdx (n = 6) mice were labeled with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 50 publications
9
63
0
Order By: Relevance
“…Hence, the analytical strategy employed in this study is a compromise between using total extracts, which may result in the underrepresentation of minor muscle proteins, and extensive prefractionation protocols, which often complicate comparative studies by unintended entrapment, desorption, or clustering of certain proteins. Our study complements previous proteomic investigations into global changes in genetic animal models of Duchenne muscular dystrophy [23][24][25][26][27]. The proteomic analysis of the enriched protein fraction from normal versus dystrophic mdx muscle has resulted in the identification of 10 novel protein species, including ferritin, transferrin, and various isoforms of the molecular chaperone Hsp70.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Hence, the analytical strategy employed in this study is a compromise between using total extracts, which may result in the underrepresentation of minor muscle proteins, and extensive prefractionation protocols, which often complicate comparative studies by unintended entrapment, desorption, or clustering of certain proteins. Our study complements previous proteomic investigations into global changes in genetic animal models of Duchenne muscular dystrophy [23][24][25][26][27]. The proteomic analysis of the enriched protein fraction from normal versus dystrophic mdx muscle has resulted in the identification of 10 novel protein species, including ferritin, transferrin, and various isoforms of the molecular chaperone Hsp70.…”
Section: Introductionsupporting
confidence: 56%
“…Although the primary abnormalities causing X-linked muscular dystrophy have been thoroughly established and the corresponding deficiency in the membrane cytoskeletal protein dystrophin is well documented, little is known about the complexity of secondary changes leading to dystrophinopathy. Previous proteomic studies have mostly focused on total tissue extracts and therefore identified mainly abundant muscle-associated proteins, such as components involved in metabolism, excitation-contraction coupling, ion handling, the cellular stress response, and stabilization of the cytoskeleton and extracellular matrix [23][24][25][26][27]30,35]. In contrast, the depletion of the contractile apparatus by differential centrifugation, as shown in this report, enables the comparative proteomic screening of minor protein species in normal versus dystrophic preparations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Procedures outlined previously for DIGE (Anderson et al, 2012;Gardan-Salmon et al, 2011) were followed, with minor modifications. For each comparison, a pooled sample, to serve as a reference, was created from an equal amount of protein from all samples for a particular tissue or muscle.…”
Section: Two-dimensional Difference In Gel Electrophoresismentioning
confidence: 99%
“…In order to unravel novel secondary molecular mechanisms, which could indicate new therapeutic targets, we decided to evaluate the protein expression profile in laminin ␣2 chain-deficient dy 3K /dy 3K muscle. Several proteomic profiling studies of dystrophindeficient muscles (Duchenne muscular dystrophy) have been performed (13)(14)(15)(16)(17)(18)(19)(20), as well as some with dysferlin-deficient muscles (Limb-girdle muscular dystrophy type 2B, Miyoshi myopathy) (21,22). They all showed a great number of proteins that were differentially expressed in different dystrophic muscles and at different ages (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%